EDITORIAL COMMENTS ON THE ARTICLE OF M.N. MAMEDOV AND M.V. STROEVA "WHAT CAN WE EXPECT USING ACE INHIBITOR RAMIPRIL IN PERSONS WITH HIGH CARDIOVASCULAR RISK AND EARLY DISORDERS OF CARBOHYDRATE METABOLISM? LESSONS OF DREAM TRIAL" - статья Редакционная (Столичная издательская компания, 2016)
.